2021
DOI: 10.3390/nu13072371
|View full text |Cite
|
Sign up to set email alerts
|

The Validity of Ultrasound Technology in Providing an Indirect Estimate of Muscle Glycogen Concentrations Is Equivocal

Abstract: Researchers and practitioners in sports nutrition would greatly benefit from a rapid, portable, and non-invasive technique to measure muscle glycogen, both in the laboratory and field. This explains the interest in MuscleSound®, the first commercial system to use high-frequency ultrasound technology and image analysis from patented cloud-based software to estimate muscle glycogen content from the echogenicity of the ultrasound image. This technique is based largely on muscle water content, which is presumed to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 54 publications
0
11
0
Order By: Relevance
“…While some studies have questioned the validity and utility of using skeletal muscle ultrasound to estimate muscle glycogen content (45,46), we successfully detected expected decreases in muscle "fuel" using the MuscleSound ® session fuel percentile score. Although our analyses did not achieve statistical significance, we observed strong directional results suggesting reduced muscle fuel following the ketogenic diet as well as following the time trial across all conditions.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…While some studies have questioned the validity and utility of using skeletal muscle ultrasound to estimate muscle glycogen content (45,46), we successfully detected expected decreases in muscle "fuel" using the MuscleSound ® session fuel percentile score. Although our analyses did not achieve statistical significance, we observed strong directional results suggesting reduced muscle fuel following the ketogenic diet as well as following the time trial across all conditions.…”
Section: Discussionmentioning
confidence: 85%
“…This method has been shown to correlate highly with glycogen content measured by muscle biopsy (29,44). However, some studies have questioned the validity and utility of this technique (45,46). In the present study, we investigated whether the MuscleSound ® system was able to detect assumed changes in muscle glycogen content resulting from dietary interventions and a 30-km time trial.…”
Section: Muscle Ultrasoundmentioning
confidence: 97%
“…Besides making predictions on total energy turnover during exercise, it is useful to establish the rate of glycogen breakdown, as very high-intensity efforts can substantially reduce muscle glycogen content without very high energy turnover rates [34,176], especially as low glycogen availability can negatively affect performance [30]. Attempts have been made to find ways to non-invasively and cost-effectively measure muscle glycogen concentrations (e.g., using ultrasound); however, to date no independently performed validation has been successful in showing that this method of muscle glycogen quantification provides valid results [177]. Currently, the best solution is to draw on previous studies investigating glycogen breakdown by muscle biopsy in different sports disciplines, such as weightlifting [178], athletics [179], rugby [180], men's football [181], women's football [182] and Australian Rules football [183].…”
Section: Personalizing Carbohydrate Intakementioning
confidence: 99%
“…For this Special Issue, research leaders in sports nutrition were approached and invited to submit current reviews in their areas of expertise [ 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 ]. The topics are novel and wide-ranging, and include updates and insights on protein [ 11 , 12 ], dietary patterns and nutritional interventions to support sleep, older athletes, and sports performance [ 13 , 14 , 15 ], pre-exercise nutrition [ 16 ], supplementation with betaine, iron, and creatine [ 17 , 18 , 19 ], and sports nutrition research methodologies for body composition and muscle glycogen analysis [ 20 , 21 ]. A major emphasis in all of the papers was a focus on strengths and weaknesses for various sports nutrition strategies, and insights for future research.…”
mentioning
confidence: 99%
“…This research group concluded that properly conducted skinfold measurements provide useful data and may be preferred over other methods because it is simple, low-cost, least affected by lifestyle confounders, and good for the long-term tracking of athletes. The measurement of muscle glycogen is important in sports nutrition studies, and Bone et al [ 21 ] cautioned that high-frequency ultrasound technology for estimating muscle glycogen content needs further development.…”
mentioning
confidence: 99%